THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND THE INCIDENCE OF STUNTED GROWTH IN INFANTS IN THE VILLAGE OF TALANGKUSKO, TUREN DISTRICT, MALANG - Fahrina, Riza Arsanty; Amalia, Rize Budi (UNIVERSITAS AIRLANGGA, 2024)
Background: Stunted is a chronic malnutrition problem caused by malnutrition in the first 1,000 days of life. One of the risk factors for stunted growth is suboptimal exclusive breastfeeding. This study aimed to determine the relationship between exclusive breastfeeding and stunted growth incidence in infants in Talangsuko Village, Turen District, Malang. Methods: This study used an analytical observational research design with a cross-sectional approach. The research sample was 118 respondents of mothers with infants aged 6-24 months in Talangsuko Village, Turen District, Malang. The measured variables are stunted status and exclusive breastfeeding. Data was collected through questionnaires and height measurements. The research data was processed using SPSS with Chi-square analysis. Results: The results showed that 16 (13,6%) child stunted, 73 respondents (61.9%) received exclusive breastfeeding, while 45 respondents (38.1%) did not receive exclusive breastfeeding. The results of the chi-square test showed that there was a significant relationship between exclusive breastfeeding and stunted growth incidence (p=0,000). Conclusion: The conclusion of this study is that there is a significant relationship between exclusive breastfeeding and stunted growth incidence in infants in Talangsuko Village, Turen District, Malang. Therefore, exclusive breastfeeding is one of the important efforts to prevent stunted growth in infants.